2019
DOI: 10.1111/anae.14795
|View full text |Cite
|
Sign up to set email alerts
|

Microcirculation and haemodynamics after infraclavicular brachial plexus block using adrenaline as an adjuvant to lidocaine: a randomised, double‐blind, crossover study in healthy volunteers

Abstract: We evaluated the effect of adrenaline when added to lidocaine in infraclavicular brachial plexus blocks on human skin microcirculation (nutritive and subpapillary) and systemic cardiovascular variables. Twelve healthy, non-smoking, male volunteers were included, each attending two study sessions two weeks apart, with a crossover design. In both sessions, they received an ultrasoundguided infraclavicular brachial plexus block in the non-dominant arm with 0.4 ml.kg -1 lidocaine 15 mg.ml -1 with or without adrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…All doses of dopamine and phenylephrine enhanced sensory blockage and prolonged the duration of nociceptive blockage by mexiletine. Relevant studies have shown that the combined application of dopamine or phenylephrine can increase the analgesic effect of local anesthetics (Chen et al 2018 ; Tzeng et al 2016 ; Hung et al 2017 ; Holmberg et al 2019 ). It has been suggested that local anesthetics suppress neural impulses by inhibiting sodium currents in the nerves (Tikhonov and Zhorov 2017 ).…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…All doses of dopamine and phenylephrine enhanced sensory blockage and prolonged the duration of nociceptive blockage by mexiletine. Relevant studies have shown that the combined application of dopamine or phenylephrine can increase the analgesic effect of local anesthetics (Chen et al 2018 ; Tzeng et al 2016 ; Hung et al 2017 ; Holmberg et al 2019 ). It has been suggested that local anesthetics suppress neural impulses by inhibiting sodium currents in the nerves (Tikhonov and Zhorov 2017 ).…”
Section: Disscusionmentioning
confidence: 99%
“…Adrenaline is a vasoconstrictor traditionally used as an adjuvant to improve the quality and duration of analgesia (Holmberg et al 2019 ), as it has been previously shown to reduce the diffusion of local anesthetics into the bloodstream (Sheikh et al 2017 ; Wiesmann et al 2018 ). Interestingly, in the current study, subcutaneous phenylephrine at a dose of 0.1473 μmol resulted in a 35.417% blockage (%MPE), which is in line with previous reports suggesting that phenylephrine itself can induce cutaneous anesthesia through the activation of various subtypes of α1-adrenoceptors (Drummond et al 2018 ).…”
Section: Disscusionmentioning
confidence: 99%